The moderating role of board ownership on the relationship between corporate governance and firm performance among the listed companies in Jordan - Qadorah, Almontaser Abdallah Mohammad (2019)
performance in Jordanian listed firms. It also explores the moderating impact of board ownership on the relationship between board of directors’ characteristics (i.e., board size, board independence, CEO duality, board meetings) and firm performance. Firm performance is measured using return on assets (ROA) and Tobin’s Q. This study covers 90 listed firms on the Amman Stock Exchange (ASE) from 2014 to 2016 (N = 270). Hierarchical regression analysis is employed to examine if board ownership moderates the relationship between board of directors’ characteristics and firm performance. The findings show that board independence, Chief Executive Officer’s (CEO) duality, board meetings, managerial ownership, foreign ownership, audit committee presence and audit firm size are significantly and positively related to ROA. However, institutional ownership, family ownership and audit fees are significantly and negatively related to ROA. The findings also show that board independence, board meetings, managerial ownership, foreign ownership, family ownership, audit committee presence and audit firm size are significantly and positively related to Tobin’s Q. However, board size and institutional ownership are significantly and negatively related to Tobin’s Q. In addition, the results show that board ownership moderates the relationship between the board of directors’ characteristics and firm performance for both models (ROA and Tobin’s Q). The findings indicate that the interaction of board ownership and board of directors’ characteristics is significantly and negatively related to firm performance. This study concludes that good corporate governance mechanisms play a key role in improving the performance of firms. The current study presents practical evidence to the policymakers, academicians and all related parties in emerging markets, specifically in Jordan.